Entre perceptions, publicisation et stratégies d’acteurs, la difficile inscription des risques littoraux dans l’action publique : focus camarguais - Aurélien Allouche; Laurence Nicolas (VertigO, 2015)
In many ways coastal risks arouse remarkable conflicts: concerning the degree of existence attributed to them and the attention they should deserve, concerning the way they are brought into the public space and at last, relatively to their treatment by the territorial adaptative land management. The authors try to figure out some relevant factors to explain the persistence of dissensions at these different levels of the social apprehension of the issue of coastal risks. At this end the authors rely on a case study situated on the coast of Camargue (south of France). This ground offers at the same time a textbook case and such a regular situation that it allows everyone to easily perceive how its main traits could be generalized. The authors aim to develop some points that are less frequently treated in the study of the social perceptions of risks and of the public politics of mitigation of the social vulnerability. The matter of this paper is to complete the analysis centered on individuals and their personal representations by the study of the physical and social context in which these representations are grounded